Electrochemical Evidence for Two Sub‐families of FeNxCy Moieties with Concentration‐Dependent Cyanide Poisoning. Issue 14 (5th March 2018) - Chung, Min Wook; Chon, Gajeon; Kim, Hyungjun; Jaouen, Frédéric; Choi, Chang Hyuck
Abstract: Iron‐nitrogen‐carbon (Fe−N−C) catalysts are one of the most promising family of materials for the successful replacement of noble Pt in low‐temperature fuel cells. Despite recent advances in the synthesis, activity, and site‐structure of Fe−N−C catalysts, further improved understanding of the nature of the Fe‐based active sites is still needed. In the present study, the existence of two sub‐families of FeN x C y moieties is revealed by the concentration dependence of cyanide poisoning on a Fe−N−C catalyst only comprising of atomically dispersed iron. The analysis of the activity decrease upon contact with various cyanide concentrations and activity recovery following rinsing with water reveals the presence of two sub‐groups of ORR‐active FeN x C y species. They are discriminated by the reversibility or irreversibility of the cyanide poisoning. From a Mössbauer spectroscopy study and poisoning test on a model compound, Fe(II) phthalocyanine (FePc), we hypothesize that the reversibility/irreversibility of cyanide poisoning is governed by the competitive adsorption of oxygen molecule and cyanide anion. It is proposed that FeN x C y moieties with Fe in low spin state reversibly adsorb cyanide, whereas those with a medium spin state irreversibly adsorb cyanide. Abstract : The presence of multiple FeN x C y species in Fe−N−C catalysts is studied with various concentrations of cyanide ions under conditions of the electrochemical oxygen reduction reaction, allowing two (or more) different types of atomic Fe sites to be observed, which are reversible or irreversible to the cyanide poisoning (see picture).